2009
DOI: 10.1007/s10856-009-3941-8
|View full text |Cite
|
Sign up to set email alerts
|

Titanates deliver metal ions to human monocytes

Abstract: Amorphous peroxotitantes (APT) are insoluble titanium-based particles that bind a variety of metal compounds with high affinity; these particles could be sequestered locally in a solid phase to deliver metal-based drugs. Previous studies have confirmed the 'biodelivery' of metals from metal-APT complexes to fibroblasts, but not monocytes. Our goal in the current study was to use monocytic cytokine secretion to assess delivery of gold or platinum-based compounds from APT to human THP1 monocytes. Cytokine secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Despite the efforts made in this respect, the achievements in controlling and sustaining the release of loaded therapeutic metal ions—in terms of obtaining constant therapeutic amount release of the ion over a period of time—have been very limited [18]. Amorphous peroxititanates (APT) might also be used to bind a variety of metal compounds with high-affinity forming complexes to control the delivery of metal-based drugs to the target tissue avoiding systemic toxicity, or to capture metal ions from body tissues [3337]. Wataha et al .…”
Section: Localized Release Of Metallic Ionsmentioning
confidence: 99%
“…Despite the efforts made in this respect, the achievements in controlling and sustaining the release of loaded therapeutic metal ions—in terms of obtaining constant therapeutic amount release of the ion over a period of time—have been very limited [18]. Amorphous peroxititanates (APT) might also be used to bind a variety of metal compounds with high-affinity forming complexes to control the delivery of metal-based drugs to the target tissue avoiding systemic toxicity, or to capture metal ions from body tissues [3337]. Wataha et al .…”
Section: Localized Release Of Metallic Ionsmentioning
confidence: 99%
“…Several years later, in a more detailed study, [14] THP1 monocytes were exposed to APT-metal compounds, but using cytokine secretion (IL6, IL1β, and TNFα.) as a measure of cellular effect [3,13].…”
Section: Effects Of Titanate Complexes On Mammalian Cellsmentioning
confidence: 99%
“…However, titanate-metal compounds have emerged as a promising new class of antimicrobials against oral and skin bacterial infections. Titanate particles bind and sequester a variety of metals with high affinity, thus would be able to deliver metals to a site of infection with less systemic toxicity [14]. To assess the utility of metal titanate compounds against bacteria, studies first focused on the effects of native titanates and metal ions alone, then investigated the ability of titanate-metal compounds to inhibit bacterial growth.…”
Section: Effects Of Titanate Complexes On Bacteriamentioning
confidence: 99%
“…In vitro tests with the noble metal-exchanged titanates indicate suppression of the growth of cancer and bacterial cells by an unknown mechanism. 8,9 Historically, sodium titanates have been produced using both sol-gel and hydrothermal synthetic techniques resulting in fine powders with particle sizes ranging from a few to several hundred microns. 4,5,10,11 More recently, synthetic methods have been reported that produced nanosize titanium dioxide, metal-doped titanium oxides, and a variety of other metal titanates.…”
Section: Introductionmentioning
confidence: 99%